Perifolliculitis capitis abscedens et suffodiens: features of diagnostics and approaches to treatment - O.L. Statkevych; T.V. Svyatenko (Medičnì Perspektivi)
The article presents a clinical case of the abscessing perifolliculitis of the head. Nowadays due to socio-economic circumstances, there is an increase in the number of patients with abscessing perifolliculitis of the head. Among the triggering factors are emergency conditions associated with chronic stress, poor hygiene, and the need to use special clothing and head protection in military personnel, which cause initial occlusion in the scalp area. Treatment is usually difficult and often unsuccessful, with regular relapses after treatment is stopped. However, the issues of diagnosing abscessing perifolliculitis of the head remain relevant and extremely difficult in the clinical practice of dermatologists and related specialists, and a single treatment protocol with clear recommendations has not yet been developed. All of the above determines the need to study the specifics of clinical and morphological manifestations in patients suffering from abscessing perifolliculitis of the head with the further aim of pathogenetic substantiation and development of complex therapy. The article aimed to improve the diagnosis and treatment of the abscessing perifolliculitis of the head by studying the clinical and anamnestic features and the course of the disease on the example of a clinical case with further implementation of recommendations in clinical practice.